2020
DOI: 10.1101/2020.05.12.20099333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

THE MUC5B PROMOTOR POLYMORPHISM ASSOCIATES WITH SEVERE COVID-19

Abstract: Background Diversity in response to exposition to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is common and may be related to the innate immune response. The mucin MUC5B is an important component of the innate immune response and expression levels are associated with the MUC5B promoter polymorphism, rs35705950. The high expressing T-allele of rs35705950 is an accepted risk allele for a non-infectious aging lung disease called idiopathic pulmonary fibrosis (IPF). However, given the theory of tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…It is intriguing that the most strongly associated IPF variant [ 9 , 11 ], rs35705950 at the MUC5B gene locus, which its risk allele (T) associated with a five-fold increase in IPF risk [9] , is negatively associated with COVID-19 regardless of severity, suggesting that this IPF risk allele may protect against COVID-19. This association has been reported in a small study [30] , and a protective role for MUC5B in airway defense has been described [31] . The IPF risk allele (T) of the rs35705950 is associated with increased MUC5B expression in lung tissue [13] , which has been associated with muco-ciliary dysfunction and increased bleomycin-induced fibrosis in mice [32] .…”
Section: Discussionsupporting
confidence: 57%
“…It is intriguing that the most strongly associated IPF variant [ 9 , 11 ], rs35705950 at the MUC5B gene locus, which its risk allele (T) associated with a five-fold increase in IPF risk [9] , is negatively associated with COVID-19 regardless of severity, suggesting that this IPF risk allele may protect against COVID-19. This association has been reported in a small study [30] , and a protective role for MUC5B in airway defense has been described [31] . The IPF risk allele (T) of the rs35705950 is associated with increased MUC5B expression in lung tissue [13] , which has been associated with muco-ciliary dysfunction and increased bleomycin-induced fibrosis in mice [32] .…”
Section: Discussionsupporting
confidence: 57%
“…However, a recent study indicated the presence of elevated levels of secreted MUC1 and MUC5AC in the sputum aspirated from the trachea of COVID-19 patients ( 62 ). COVID-19 patients also have a lower allelic frequency of the MUC5B genetic variant rs35705950 than healthy controls, which is associated with a higher level of expression of MUC5B, suggesting a protective role for MUC5B ( 63 ). The role of soluble and transmembrane mucins and their glycans during COVID-19 pathogenicity needs to be addressed to fully understand the course of the disease ( Fig.…”
Section: Mucosal Defense Against Sars-cov-2mentioning
confidence: 99%
“…The allele rs35705950*T, a risk factor for IPF, was associated with protection against the development of severe COVID-19 in older adults ( Fadista et al, 2021 ). The observed association with rs35705950 could be due to a protective effect of high mucin production in the airways, but the authors could not rule out a patient selection bias associated with the rs35705950 SNP ( van Moorsel et al, 2020 ) Other mucin family members might also be candidates for studies of COVID-19 complications in the gut and airways.…”
Section: Host Genetics Beyond Hla and Kirmentioning
confidence: 99%